Structural Barriers and Facilitators to Green Innovation in BRICS+ Countries - Dr Samuel Bangura; Dr Wiza Munyeka (Rescollacom (Research Collaborations Community), 2025)
Green innovation has emerged as a strategic imperative for balancing economic growth with environmental sustainability, especially within BRICS+ nations such as Brazil, Russia, and India. These rapidly industrializing economies face escalating ecological pressures while navigating distinct structural, institutional, and policy landscapes that influence their capacity for eco-innovation. This study adopts a qualitative integrative literature review to examine the barriers and facilitators shaping green innovation across these countries. Drawing on 35 peer-reviewed articles and empirical studies published between 2007 and 2024, the research synthesizes interdisciplinary insights into the socio-economic and regulatory dynamics that drive or hinder sustainable technological progress. Findings reveal that Brazil’s green innovation is constrained by underfunded institutions and limited academia-industry collaboration, yet bolstered by market incentives and sectoral initiatives. Russia contends with bureaucratic inefficiencies and weak regulatory enforcement but benefits from university partnerships and targeted state programs. In India, systemic issues like inadequate institutional support and lax enforcement impede progress, though recent policy reforms and growing corporate responsibility offer momentum. The study also found that green innovation is essential for sustainable growth in BRICS+ countries—Brazil, Russia, India, China, South Africa, Saudi Arabia, UAE, Egypt, Ethiopia, Iran, and Indonesia where recent research highlights distinct structural barriers and facilitators influencing its adoption and impact on environmental and economic outcomes. Thematic content analysis categorizes these influences and highlights recurring patterns and country-specific distinctions. Triangulation across sources enhances validity and ensures a comprehensive perspective.